Konsep Co-Management dalam Pendekatan Pengelolaan Lingkungan Mangrove di Desa Lubuk Kertang, Brandan Barat, Sumatera Utara - A Hadian Pratama Hamzah; Trisno Anggoro; Sri Puryono (Universitas Batanghari, 2020)
Mangroves are one of the important coastal ecosystems that have various benefits and their uses are carried out by various stakeholders. This study aims to 1) find out and analyze the condition of mangrove resources and community beneficiaries, 2) analyze the roles and functions of each stakeholder, and 3) find out and analyze the form of co-management of mangrove ecosystem management in Lubuk Kertang Village, West Brandan, Langkat Regency. Mangrove vegetation data collection is done using the quadratic transect method; while taking socioeconomic, institutional, and interview data using survey and purposive sampling methods. Data obtained from mangrove vegetation include density, frequency, cover, and mangrove importance index. Stakeholder analysis using a matrix of interests and influences. Research shows there are 5 types of mangroves in Lubuk Kertang Village, namely Avicennia marina, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa and Sonneratia alba. Strategies in the context of expanding mangrove forests are with these types. Stakeholder analysis identified 16 stakeholders who were classified in 4 groups, namely subject, key players, crowd, and by standers. Mangrove management in Lubuk Kertang Village is still in the consultative stage. To improve effectiveness, management is directed at the cooperative level in the co-management spectrum with management strategies.